Analysis of the Professional Competency Capabilities of Certified and Uncertified Religious Subject Teachers - Fadhilah Khairiyah; Siti Halimah; Mara Samin Lubis (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
This study aims to examine the professional competence skills of certified and non-certified religious subject teachers, as well as techniques for enhancing religious subject teachers' professional competency in Madrasah Aliyah Negeri (MAN) across Pematang Siantar Municipality. This study is qualitative research that employs descriptive analysis. Data-collecting methodologies include questionnaires, test instruments, interview guidelines, observation guidelines, and scales. Methods of data collection include observation, interviews, and documentation studies. The research findings indicate that 1) the professional competence of certified religious subject teachers in mastering the material, structure, concepts, and scientific mindset that supports the subjects taught is in the good category; in mastering the competency standards and basic competencies of the subjects taught is in the good category; and in developing learning materials that are taught creatively is in the poor category, because more teachers are over 50 years old; 2) Religious topic instructors' professional competency capabilities in grasping the content, structure, ideas, and scientific mentality that supports the subjects taught in the very good category have not been accredited; 3) Strategy for developing the professional competence of religious subject teachers at MAN Pematang Siantar in developing professionalism on an ongoing basis through reflective actions is in a good category; using information and communication technology to develop oneself is also in the good category. Teacher competency, particularly teacher professional competence, should be enhanced further in order to produce teachers who are professional as a whole.